TES KETERAMPILAN OLAHRAGA JUDO BAGI MAHASISWA - PIDA, JUMHAN (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2015)
Abstract The research is aimed to construct judo skill test for students, considering there has not been any judo skill test up to the present time. The sample students are the students of the dojo of UNY, taken purposively. The test is constructed in two skill groups, namely Kogo Uchikumi Nage Waza (throwing technique group) and Kogo Uchikumi Katame Waza (gripping technique group). The first group is done by Kogo Uchikumi( variety of technique) namely: (1) one place position, (2) moving backward, (3) moving forward, (4) moving sideward, in 30’ for each variation of technique. Each of the techniques needs 45’, 900 and 1800 of pivoting the body alternatively without going through throwing the second group is done by techniques of gripping the body, arm and neck, alternatively in 30’ the lying position on the mat. Keywords: kogo uchikumi, judo skill